Hidden in the leaf litter: rediscovery of the Largescale Lizard, Alopoglossus grandisquamatus (Rueda, 1985) (Squamata: Alopoglossidae) with comments on novel morphological variation - Lozano-Arias, Juan M.; Gómez-Mesa, Laura; Durango, Juan P.; Franco, Esteban Garzón- (Zootaxa, 2026)
Alopoglossus grandisquamatus is a species only known from its male holotype, collected almost 40 years ago. We report the rediscovery of the Largescale Lizard A. grandisquamatus based on two female individuals from two new localities, extending its known distribution 19 km eastwards and 100 km southwards. Conservation status of Endangered is proposed for A. grandisquamatus. Novel morphological variation is described, including sexual dimorphism in femoral pores. Synonymy of A. grandisquamatus with Alopoglossus eurylepis is discussed, with the dismissal of non-useful diagnostic characters. New characters such as number of femoral pores in males, gular scales arrangement and the number of transversal rows of ventral scales are proposed to diagnose A. grandisquamatus from A. eurylepis. Other characters used by previous authors to differentiate both species are also validated.